Wide gap between knowledge and practices: a cause of concern for high prevalence of hypertension among lower socioeconomic class among urban slum population - Joshi, Mohan P.; Puri, Mahesh A.; Ausvi, Samina M.; Saoji, Ajeet V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Being an important public health problem, increasing the awareness and changing the attitudes regarding hypertension among masses would definitely help in reducing its morbidity and mortality. The study was planned with the aim to study the knowledge, attitude, practices and the prevalence of hypertension and related different socio-demographic factors. Methods: A cross-sectional study was conducted among 280 adults aged above 18 years at an urban slum in Nagpur during January 2016 to June 2017. The collection of data and the measurement of the blood pressure were done as per protocol and analysis was done. Results: Among the total 280 study subjects, the majority of 149 (53%) participants were in the age group of 41 to 60 years and majority of 250 (89%) participants were from class IV and V. Among the study subjects, around 178 (64%) were tobacco and alcohol consumers. There was statistically significant association of hypertension with alcohol and tobacco consumption, physical activities at workplace, SES class and family history of hypertension amongst them. Though, 62% of the participants had good knowledge regarding hypertension, only 54% were having positive attitude regarding it. But barely 42.75% of the participants were actually practicing those healthy practices. Conclusions: This difference in knowledge and practices is expected to have its impact on the morbidity and mortality of hypertension amongst the masses. There seems to be an urgent need for providing diagnostic and treatment facilities at primary healthcare level, including the need of health education regarding risk factors causing hypertension.